Depression Before and After a Diagnosis of Pancreatic Cancer: Results From a National, Population-Based Study. Issue 8 (September 2020) - Seoud, Talal; Syed, Aslam; Carleton, Neil; Rossi, Caitlan; Kenner, Barbara; Quershi, Hassan; Anand, Mary; Thakkar, Payal; Thakkar, Shyam
Abstract : Objectives: The aim of this study was to evaluate depression in pancreatic cancer (PC) patients before and after a cancer diagnosis using a US-based healthcare database. We also sought to study the impact of treatment of depression in PC patients on all-cause mortality. Methods: Pancreatic cancer patients with comorbid depression in Explorys (1999–2019) were compared with controls using odds ratios with 95% confidence intervals. Rates of depression diagnosed within 6 months, 1 year, and 3 years before and after a PC diagnosis were recorded. Patients who developed depression after a PC diagnosis were further categorized into those treated for depression using mental health professionals (MHPs), pharmacologic treatment, or both (2015–2019). Results: Of the 62, 450 PC patients, 10, 220 (16.4%) were diagnosed with depression before PC and 8130 (13%) were diagnosed with depression after PC. Patients diagnosed with depression after PC had a significantly higher all-cause mortality than patients with PC alone ( P < 0.0001). Involvement of MHP significantly improved all-cause mortality ( P = 0.0041). Conclusions: Most post-PC depression is diagnosed in the first 6 months after a PC diagnosis. Although depression significantly increases PC mortality, integrating MHP in the care of PC patients with depression improves outcomes. Abstract : Supplemental digital content is available in the text.